THE ANALYSIS OF VERBAL AND VISUAL SIGNS IN HORROR MOVIE POSTERS - Ni Ketut Dewitri; I Made Yogi Marantika (Language and Education Journal Undiksha, 2023)
This study was aimed at analyzing the meaning of verbal and visual signs used in horror movie posters. This study analyzed horror movie posters because they are important tools in marketing of a product and horror movies have big enthusiasts all around the world. The observation method was used in this study to collect data. The data for this study came from two horror movie posters: Annabelle Comes Home (2019) and The Curse of La Llorona (2019). The data were collected by watching the movie to find out the story behind the movie posters, downloading the movie posters via internet, reading and making a note of the important information related to the topic, then identifying and classifying the data into verbal and visual signs to determine the meaning of the data. The study were described and interpreted using three theories. The first theory used was Saussure's theory in Chandler’s (2007:14) to identify verbal and visual signs, second theory from Barthes (1977) about denotative and connotative meaning, and finally a theory from Cerrato (2012) about colour meanings. The result of analysis shows these horror movie posters have eleven verbal signs and seven visual signs. Six verbal signs and three visual signs were found in Annabelle Comes Home movie poster, five verbal signs and four visual signs in The Curse of La Llorona movie poster. This study also found denotative and connotative meanings from those horror movie posters.